Effect Of Work Discipline And Work Environment On Teacher Performance Tarbiyatul Mu'allimin Foundation - Rachma Septiawan; Arga Sutrisna; Kusuma Agdhi Rahwana (Penerbit Jurnal Indonesia, 2022)
Education in the 4.0 era uses information technology so that it demands an increase in the quality of facilities and infrastructure including human resources, especially teachers who can support improving the quality of basic education. Education plays an important role in life and becomes the basis for improving superior human resources. One of them is to focus on students by utilizing digital media technology, and using innovative approaches (Kemendikbud, 2018). Tarbiyatul Mu'allimin Foundation as a school providing education at the madrasah group level Tsanawiyah (Mts) to Madrasah Aliyah (MA) are one of the schools that take part in education in Indonesia, especially in Tasikmalaya Regency. There is a change in the teaching and learning process, so coordination is needed in all elements. Currently the KBM process runs offline and the leadership of the principal is needed to achieve an adequate learning process. This study aims to determine the effect of work discipline and work environment on teacher performance at Tarbiyatul Mu'allimin Foundation. The research method uses the causal associative method with a survey approach, the survey in this study to teachers of the Tarbiyatul Mu'allimin Foundation as many as 32 respondents. The data used are primary and secondary data. The data analysis technique used is Multiple Linear Regression Analysis using SPSS v.25 Software. The results of the hypothesis testing of work discipline and work environment have a significant effect on teacher performance at the Tarbiyatul Mu'allimin Foundation teacher partially and simultaneously